Management of parapneumonic empyema in children - Cekirdekci, A.; Koksel, O.; Goncu, T.; Burma, O.; Rahman, A.; Uyar, I.S.; Uysal, A. (Asia Publishing Exchange Pte Ltd, 2000)
Empyema is a serious complication of bacterial pneumonia in children. Between July 1992 and July 1998, 53 children aged 7 months to 12 years (mean age, 5.5 years) were treated for empyema complicating pneumonia. After diagnostic thoracentesis, closed tube drainage was carried out with appropriate antibiotic therapy and other treatment strategies such as pleural lavage, intrapleural enzymatic debridement, decortication, or pulmonary resection, according to the effectiveness of drainage and clinical status. There was one death from toxic shock. It was concluded that early decortication in the chronic stage of the disease is a safe and effective treatment modality.
Keywords: antibiotic agent; article; bacterial pneumonia; child; debridement; decortication; empyema; female; human; infant; lung lavage; lung resection; major clinical study; male; retrospective study; septic shock; Staphylococcus aureus; thoracocentesis; thorax radiography